Recent advancements in strategies to improve performance of tungsten-based semiconductors for photocatalytic hydrogen production: a review - Mim, R. S. (IOP Publishing Ltd., 2021)
Multiple efforts have been made to find and utilize sustainable renewable energy to replace fossil fuels that have polluted the environment. Among many semiconductors, tungsten trioxide (WO3) is a promising semiconductor due to its narrow band gap (between 2.5 and 3 eV) and has stable chemical and physical properties. WO3 can absorb a broad range of the solar light spectrum but it is unable to produce hydrogen from water due to its lower conduction band position. However, the high oxidation power of the valence band; nontoxicity and resiliency towards harsh environments such as continuous contact to water and solar irradiation makes it a very promising photocatalyst. The current review article is a literature review on the basis of keywords including hydrogen production; tungsten-based semiconductors; heterojunction formation; band gap engineering, thermodynamics and visible light active photocatalysts. This review aims to summarize the current progress in WO3 based materials for photocatalytic H2 production along with the recent strategies employed for modifications of WO3 based materials for efficient photoactivity. Conventionally, the fundamentals along with the thermodynamics for photocatalytic hydrogen production based on heterogeneous photocatalysts have been discovered. The structural modifications of WO3 with band gap engineering for efficiency enhancement are systematically presented. Recent approaches such as coupling of semiconductors, band gap engineering, establishment of heterojunctions, Z-scheme and step-scheme development to improve the surface sensitization of a semiconductor have been thoroughly discussed. Co-doping semiconductors have proven to reduce the band gap notably and their outstanding electronic band position for visible light photocatalysis has been identified. Modification, doping or coupling of WO3 with a cocatalyst is necessary to change the band gap position. This review article summarizes progress of modifications of WO3 and discusses the future research direction for designing the most efficient WO3 composite towards hydrogen production